Construction et mise en œuvre d'un doctorat international : des enjeux aux problèmes. Le cas des doctorats Erasmus Mundus - Magali Hardouin
The paper contributes to the analysis of training courses built jointly between higher education institutions in different countries through the analysis of the Erasmus Mundus doctoral programme (2009-2013). This programme aimed, through courses built by consortia of higher education institutions in Europe and around the world, to attract very good doctoral candidates from third countries to the European Union. It sought to counterbalance North American influence in the field of training and research, and also illustrates the EC's desire to spread its model of higher education, considered excellent, throughout the world.Based on a methodology based on a dual approach (exploitation of databases, consolidated by data collected through questionnaires and interviews), the paper aims to show that this programme, proposed by the EC, with strong political and economic connotations, meets with the support of many actors who see a clear interest. However, it must also be noted that many questions, errors of thought and resolution beforehand, at the European level, make it very difficult to structure and manage this original training at the local level and do not ultimately make it possible to satisfactorily meet the pre-defined objectives.